Mad CoW: A Reply to Gibler and Miller. - Lyall, Jason (International Studies Quarterly, 2022)
In Divided Armies , I argue that inequality within armies ("military inequality") has shaped their battlefield performance in conventional wars since 1800. Gibler and Miller (2022) are unpersuaded. They raise a flurry of concerns about the cross-national evidence and one statistical analysis in the book's Chapter 4. In particular, they maintain that Project Mars, the book's dataset, offers nothing new compared to the Correlates of War (CoW). I find their criticisms misplaced. I use their own statistical models for reanalyzing Project Mars to demonstrate that military inequality is an important driver of battlefield performance across six different measures in all types of CoW wars over the past 200 years. We should build, not bury, a research program that further explores the relationship between inequality and political violence.